In silico study of anti-cancer activity (neuroblastoma) of some metabolites of marine sponges - Bensenouci, Sabrina; Benlahbib, Hafsa; Benarous, Khadidja (Laghouat : Université Amar Telidji - Département de biologie, 2023)
Neuroblastoma (NB) is the most frequent malignant solid tumor in children derived from primordial neural crest cells and accounts for 15% of childhood cancer mortality. Several clinical trials are still underway to identify specific drugs for the treatment of this exceptional cancer. Agelas sp. has proven to serve as a biochemical storage for secondary metabolites such as alkaloids including pyrroleimidazole alkaloids (PIAs) which constitute a highly diverse and densely functionalized subclass of marine natural products with an intense biologic activity. The present study aimed to examinate in silico the ability of five Agelas sp. alkaloids, such as Ageladine A (Mol1), Oroidin (Mol2), Strepoxazine A (Mol3), Cyclooroidin (Mol4), and Taurodispacamide A (Mol5) in order to inhibit six neuroblastoma targets including; the focal adhesion kinase 1 (FAK), the caspase-3, the phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit gamma isoform (PI3K), the telomerase reverse transcriptase (TERT), the osm-9-like TRP channel 1 (TRPV1), and the RAC-alpha serine/threonine-protein kinase (AKT1). Molecular docking (Md) analysis was performed using AutoDock Vina (ADV) and Auto Dock Tools (ADT), Md results were further analyzed with Discovery Studio Visualizer (DSV) v2017, and then a pharmacokinetic (pK) study was performed to verify the inhibitors safety, using SwissADME and pre-ADMET servers. The results show that all compounds displayed significant inhibition towards neuroblastoma targets compared with their controls. Mol3 was ranked as the best inhibitor among the five inhibitors based on its binding energy of -9.5 kcal/mol, in addition to having an appropriate pK profile; its toxicity was adequate and ranked it first in this context. The other compounds were moderate; their binding energy ranged from -6.9 kcal to -8.8 kcal/mol with a moderate pK profile, indicating their strict use as their toxicity was significant. These results are promising, although the efficacy of these inhibitors needs to be confirmed in vitro and in vivo.